Highly pathogenic avian influenza viruses in mammals: host-range expansion and implications of milk-borne viral shedding - Leila Wogick; Sagar M. Goyal (Clinical Microbiology Reviews, 2026)
SUMMARY Highly pathogenic avian influenza (HPAI) viruses, especially subtype H5N1, have caused major outbreaks in poultry and serious human infections since the first description of “fowl plague” in 1878. Over time, these viruses have expanded their host range, causing huge losses in domestic poultry, spreading among wild bird populations, and occasionally infecting humans. Understanding how influenza viruses adapt and cross species barriers depends on analyzing their fundamental molecular characteristics. Key features such as the polybasic cleavage site within the hemagglutinin protein and the distinctive “1+7” ribonucleoprotein complex, which consists of a single polymerase core surrounded by seven RNA segments, enhance viral replication and broaden host range. Despite decades of intervention, including lessons from the 1997 Hong Kong outbreak and the continued global circulation of clade 2.3.4.4b, HPAI remains difficult to control. A major shift occurred in 2024, when H5N1 was detected in U.S. dairy cattle. This was the first confirmed instance of viral shedding into milk from a mammalian host, suggesting a new potential route of transmission beyond the traditional avian reservoirs. This review unites historical milestones, structural insights, epidemiological data, and recent cross-species findings to better define the current landscape of risk and transmission. We further discuss economic, public health, and agricultural impacts of these developments, particularly the 2024 cattle cases, and underscore the urgent need for an integrated One Health approach to better manage the growing risks posed by HPAI viruses.